Analysis Of Factors Affecting Financial Performance In Construction Sector Bumn Companies 2017-2022 - Faizal Rahmad; Dudi Rudianto (Sean Institute, 2024)
The aim of this research is to investigate whether corporate governance mechanisms, solvency, and corporate social responsibility simultaneously influence the financial performance of state-owned enterprises (SOEs) in the construction sector. The data used are from SOE companies in the construction sector in Indonesia listed on the Indonesia Stock Exchange (IDX) for the years 2017-2022. The research employs a quantitative method with an associative approach. The analytical model begins with tabulating and categorizing quantitative data, followed by testing the data's normality using Eviews 9 software. Subsequently, classic assumption tests were conducted to obtain unbiased best linear estimators, and panel data regression estimation is performed using the common effect model, fixed effect model, and random effect model approaches. The research results reveal that public ownership and debt to asset ratio have a significant negative impact on financial performance, institutional ownership and debt to equity ratio have a significant positive impact on financial performance, and there is no significant impact of the global reporting initiative on financial performance. Thus, it can be concluded that corporate governance mechanisms, solvency, and corporate social responsibility have a significant simultaneous impact on the financial performance of state-owned enterprises in the construction sector.